Hacia la comprensión de las expresiones del fenómeno religioso actual - Rojas Cadena, Leonardo (2023)
Religious faiths and metaphysical systems seek to give complete answers to man, and the resurgence of what is sacred, divine, and holy appears to be the last foundation on which to base an understanding of reality, and infer directions for action which is consistent with this vision in a social context. Religion is linked not only to reason, but above all, desire, experience, and the most profound experiences. In it, humans express their respect, trust, faith and hope. That which is sacred places the human being in the presence of a dimension or reality, which is superior, more profound, and unknown, and before which the self reacts more than conscious reason. In the same way that it seems not to be possible to have a sacred experience without the sensitivity and refinement which gives ‘meaning’ to the experience, neither does it seem possible to have a religious experience with no experience of what is sacred. Only when the experience of the “Mystery” is present is there religious experience, and religion is given as an answer.